Performance of the CORE‐10 and YP‐CORE measures in a sample of youth engaging with a community mental health service. Issue 4 (12th January 2016) - O'Reilly, Aileen; Peiper, Nicholas; O'Keeffe, Lynsey; Illback, Robert; Clayton, Richard
Abstract: This article assesses the performance and psychometric properties of two versions of the Clinical Outcomes in Routine Evaluation (CORE) measures that assess psychological distress: the Young Person's CORE (YP‐CORE) for 11–16 year olds and the CORE‐10 for those 17 or older. The sample comprised 1592 young people aged 12–25 who completed the YP‐CORE and CORE‐10 during their initial engagement with an early intervention service. Total and average scores were examined for both measures. Gender and age differences were evaluated using t ‐tests and analysis of variance. The factor structures were assessed with principal axis and confirmatory factor analyses. Multigroup confirmatory factor analyses were then employed to evaluate measurement invariance across age and gender. Analyses were supportive of the CORE measures as reliable instruments to assess distress in 12–25 year olds. Based upon eigenvalues in combination with the comparative fit index, the Tucker–Lewis Index, and the root‐mean‐square error of approximation, both measures were unidimensional. Analysis indicated the factor structure, loadings, item thresholds, and residuals were invariant across age and gender, although partial support for strict invariance was found for gender among 12–16 year olds. Results are compared to previous studies and discussed in the context of program planning, service delivery, and evaluation. Copyright © 2016 John Wiley & Sons, Ltd.